Komagataella phaffii as Emerging Model Organism in Fundamental Research - Bernauer, Lukas; Radkohl, Astrid; Lehmayer, Leonie Gabriela Katharina; Emmerstorfer-Augustin, Anita (Frontiers in Microbiology, 2021)
Komagataella phaffii (Pichia pastoris) is one of the most extensively applied yeast species in pharmaceutical and biotechnological industries, and, therefore, also called the biotech yeast. However, thanks to more advanced strain engineering techniques, it recently started to gain attention as model organism in fundamental research. So far, the most studied model yeast is its distant cousin, Saccharomyces cerevisiae. While these data are of great importance, they limit our knowledge to one organism only. Since the divergence of the two species 250 million years ago, K. phaffii appears to have evolved less rapidly than S. cerevisiae, which is why it remains more characteristic of the common ancient yeast ancestors and shares more features with metazoan cells. This makes K. phaffii a valuable model organism for research on eukaryotic molecular cell biology, a potential we are only beginning to fully exploit. As methylotrophic yeast, K. phaffii has the intriguing property of being able to very efficiently assimilate methanol as a sole source of carbon and energy. Therefore, major efforts have been made using K. phaffii as model organism to study methanol assimilation, peroxisome biogenesis and pexophagy. Other research topics covered in this review range from yeast genetics including mating and sporulation behavior to other cellular processes such as protein secretion, lipid biosynthesis and cell wall biogenesis. In this review article we compare data obtained from K. phaffii with S. cerevisiae and other yeasts whenever relevant, elucidate major differences, and, most importantly, highlight the big potential of using K. phaffii in fundamental research.